Pasantía en la supervisión y control de la ampliación de la etapa III del teatro Cristóbal Colón de Bogotá, ejecutada por la empresa constructora Varela Fiholl & CIA SAS y el Consorcio Cantini, (2021)
For the monitoring and control of the activities carried out in the expansion of the Cristóbal Colón Stage III Theater, the collaboration of qualified and trained personnel in the area of civil engineering, architecture or professions is required; For this reason, the tenth semester student Yustahal Ehilboy Espitia Cortes of the Antonio Nariño University is contacted to fulfill the position of engineering assistant, this in order to strengthen technical supervision in the different processes according to the schedule of work activities and contributing knowledge acquired in academic training that serves to optimize processes.